Validasi Data Satelit Tropical Rainfall Measurement Missiondengan Menggunakan Pengamatan Curah Hujan - Rafika Andari; Nurhamidah (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The availability of hydrological data poses a challenge in water infrastructure development. Common issues in this domain often arise due to the lack of comprehensive data availability. Utilizing high-resolution satellite-based rainfall measurements covering extensive areas presents a potential solution. However, variations in the observed rainfall data resolution may impact the accuracy of the data. This study employs Tropical Rainfall Measurement Mission (TRMM) rainfall data and compares it with rainfall data from observation stations to assess the suitability of TRMM as a hydrological data source. Validation analysis is conducted using the Root Mean Squared Error (RMSE), Nash-Sutcliffe Efficiency (NSE), Correlation Coefficient (R), and relative bias (RB) methods. Validation results indicate that corrected TRMM data yields better outcomes compared to uncorrected TRMM data, with lower RMSE, higher NSE, and increased RB values. The most favorable findings occur at the Batu Busuk station, with RMSE = 22.554, NSE = 0.181, R = 0.95, and RB = 0.413. These findings suggest thatcorrected TRMM data can be effectively used as a hydrological data source in water infrastructure development